Isoelectronic Pt(ii)– and Au(iii)–N-heterocyclic carbene complexes: a structural and biological comparison. (30th May 2018) - Rana, Bidyut Kumar; Mishra, Snehasis; Sarkar, Deblina; Mondal, Tapan Kumar; Seth, Saikat K.; Bertolasi, Valerio; Das Saha, Krishna; Bielawski, Christopher W.; Isab, Anvarhusein A.; Dinda, Joydev
Abstract : To differentiate the intrinsic biological activities displayed by Pt vs. Au reagents, a series of square planar carbene complexes were compared. Abstract : To elucidate the intrinsic biological activities displayed by platinum versus gold-based organometallic reagents, the isoelectronic and isostructural square planar complexes [Pt(C∩N)(C)Cl][PF6 ] (2 ) and [Au(C∩N)(C)Cl][PF6 ]2 (3 ), which are supported by a common N-heterocyclic carbene, 1-methyl-2-pyridin-2-yl-2 H -imidazo[1, 5- a ]pyridin-4-ylidene (1 ), were synthesized. The complexes were characterized using a range of spectroscopic techniques as well as single crystal X-ray diffraction and a series of computational studies were also performed to gain additional insight into their fundamental electronic bonding structures. The cytotoxicities of the complexes were tested in vitro against non-small lung carcinoma (A549), colorectal carcinoma (HCT-116) and human hepatocellular carcinoma (HepG2) cell lines. The measured IC50 values showed that the Au(iii )–NHC complex is more potent than its Pt analogue.